3 in 35 - Eldem, Murat; Yilmaz, Tuna (Eldem, Murat ; Yilmaz, Tuna, 2008)
Verzio FF Submission A documentary is about three foreigners living and working in Izmir, Turkey. Jenny - an American teacher, Koen - a Belgian businessman, and Andrea - an Italian engineer, talk about their lives, loves and experiences. 3 in 35 (the traffic code for Izmir City) aims to display the big city life through the words of these people far away from their homelands.